The Effect of Brand Positioning, Brand Image, and Perceived Price on Consumer Repurchase Intention Low-Cost Carrier - Dewa Ayu Abhinandati Prajna Pratisthita; Putu Gde Arie Yudhistira; Ni Ketut Wiwiek Agustina (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: This study aims to examine the effect of brand positioning, brand image, and perceived price on the repurchase intention of low-cost carrier consumers. Design/Methods/Approach: This study uses a purposive sampling technique to obtain a sample of 400 respondents who had used Citilink airline from I Gusti Ngurah Rai Airport. Data collection techniques are carried out by distributing online questionnaires using a Likert Scale points 1 to 5, which have been analyzed using SmartPLS 4 through the measurement model test (outer model), and structural model test (inner model). Findings: The findings show that brand positioning has a positive effect on the repurchase intention of consumers of a low-cost carrier, brand image has a positive effect on the repurchase intention of consumers low-cost carrier, and the perceived price has a positive effect on the repurchase intention of consumers low-cost carrier. Originality: This research adds dimensions to the variables of brand positioning, brand image, and perceived price and combines them to determine their effect on the repurchase intention of Indonesian low-cost airlines. Practical/Policy Implications: Identifying the results of the variable brand positioning, brand image, and perceived price can measure repurchase intention for low-cost carrier consumers. This study provides low-cost carriers that the right brand positioning strategy, positive image, and price can create a consumer repurchase intention.